Optimization and In Vivo Profiling of a Refined Rat Model of Walker 256 Breast Cancer Cell-Induced Bone Pain Using Behavioral, Radiological, Histological, Immunohistochemical and Pharmacological Methods - Shenoy, Priyank; Kuo, Andy; Vetter, Irina; Smith, Maree T. (Frontiers in Pharmacology, 2017)
In the majority of patients with advanced breast cancer, there is metastatic spread to bones resulting in pain. Clinically available drug treatments for alleviation of breast cancer-induced bone pain often produce inadequate pain relief due to dose-limiting side-effects. A major impediment to the discovery of novel well-tolerated analgesic agents for the relief of pain due to bony metastases is the fact that most cancer-induced bone pain models in rodents relied on the systemic injection of cancer cells, causing widespread formation of cancer metastases and poor general animal health. Herein, we have established an optimised, clinically relevant Wistar Han female rat model of breast cancer induced bone pain which was characterised using behavioural assessments, radiology, histology, immunohistochemistry and pharmacological methods. In this model that is based on unilateral intra-tibial injection (ITI) of Walker 256 carcinoma cells, animals maintained good health for at least 66 days post-ITI. The temporal development of hindpaw hypersensitivity depended on the initial number of Walker 256 cells inoculated in the tibiae. Hindpaw hypersensitivity resolved after approximately 25 days, in the continued presence of bone tumours as evidenced by ex vivo histology, micro-computed tomography (µCT) scans and immunohistochemical assessments of tibiae. A possible role for the endogenous opioid system as an internal factor mediating the self-resolving nature of breast cancer-induced bone pain was identified based upon the observation that naloxone, a non-selective opioid antagonist, caused the re-emergence of hindpaw hypersensitivity. Bolus dose injections of morphine, gabapentin, amitriptyline and meloxicam all alleviated hindpaw hypersensitivity in a dose-dependent manner. This is a first systematic pharmacological profiling of this model by testing standard analgesic drugs from four important diverse classes, which are used to treat cancer induced bone pain in the clinical setting. Our refined rat model more closely mimics the pathophysiology of this condition in humans and hence is well-suited for probing the mechanisms underpinning breast cancer induced bone pain. In addition, the model may be suitable for efficacy profiling of new molecules from drug discovery programs with potential to be developed as novel agents for alleviation of intractable pain associated with disseminated breast cancer induced bony metastases.